Challenges of Islamic Religious Education in the Digital Age: Building Harmony between Traditional Authority and Technological Algorithms - Farida, Umma; Wardani, R. Yani'ah Eddy; Kasdi, Abdurrohman; Atqia Rahman, Azka Fayyad (EDUKASIA, 2026)
This article aims to outline the challenges of Islamic religious education in the digital age and analyze the shift in Islamic religious education from classical learning sources based on Islamic books and traditional authorities, such as religious teachers and ulama, to technological algorithms. It also proposes solutions for building harmony between these traditional authorities and digital technology. This research method used a Systematic Literature Review (SLR) involving the collection and analysis of data from various relevant sources, such as books, journal articles, research reports, and digital sources that discuss the challenges of Islamic Religious Education (PAI) learning in the digital age, the shift in authority in social media, and proposed solutions for harmonizing traditional authority with technological algorithms. The research results indicate that technological algorithms have a positive impact on increasing student interest in Islamic Religious Education (PAI), by providing more visual and interactive material presentation, enhancing broader accessibility, enriching Islamic religious education materials, and improving the quality of learning. Negative impacts include internet addiction, vulnerability to false information or hoaxes, and low digital and religious literacy exploited by deviant content. Harmonizing traditional authority and technological algorithms in Islamic religious education requires strengthening digital and religious literacy. Digital literacy here is not only about technical skills in using devices and applications, but also the ability to filter information that is credible, objective, and scientifically grounded.